3D model of the campus of Universiti Teknologi Malaysia using google sketchup [electronic resource] - Ten,Ti Feng, 1988-. author; Fakulti Geoinformasi dan Harta Tanah (2011)
Project Paper (Sarjana Muda Kejuruteraan (Geomatik)) - Universiti Teknologi Malaysia, 2011